2021
DOI: 10.1080/22221751.2021.1969868
|View full text |Cite
|
Sign up to set email alerts
|

Host-dependent editing of SARS-CoV-2 in COVID-19 patients

Abstract: A common trait among RNA viruses is their high capability to acquire genetic variability due to viral and host mechanisms. Next-generation sequencing (NGS) analysis enables the deep study of the viral quasispecies in samples from infected individuals. In this study, the viral quasispecies complexity and single nucleotide polymorphisms of the SARS-CoV-2 spike gene of coronavirus disease 2019 (COVID-19) patients with mild or severe disease were investigated using next-generation sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 56 publications
(72 reference statements)
1
17
1
Order By: Relevance
“…We agree that this can be further optimized and, indeed, subsequent studies proposed more refined approaches to reduce the number of false positive calls (e.g., (Picardi and Mansi 2022 )). It is indeed reassuring that different pipelines converged to the same conclusions (Di Giorgio et al 2020 ; Farkas et al 2020 ; Popa et al 2020 ; Wang et al 2021 ; Graudenzi et al 2021 ; Gregori et al 2021 ; Lythgoe et al 2021 ; Pathak et al 2021 ; Song et al 2021 ; Tonkin-Hill et al 2021 ; Voloch et al 2021 ). While we agree that the mutational spectrum is not significantly affected by the filters reanalyzed by Zong et al ( 2022 ), these filters were nonetheless necessary to avoid introducing bias in the estimation of the allelic fraction of the observed changes.…”
Section: Main Textmentioning
confidence: 87%
See 3 more Smart Citations
“…We agree that this can be further optimized and, indeed, subsequent studies proposed more refined approaches to reduce the number of false positive calls (e.g., (Picardi and Mansi 2022 )). It is indeed reassuring that different pipelines converged to the same conclusions (Di Giorgio et al 2020 ; Farkas et al 2020 ; Popa et al 2020 ; Wang et al 2021 ; Graudenzi et al 2021 ; Gregori et al 2021 ; Lythgoe et al 2021 ; Pathak et al 2021 ; Song et al 2021 ; Tonkin-Hill et al 2021 ; Voloch et al 2021 ). While we agree that the mutational spectrum is not significantly affected by the filters reanalyzed by Zong et al ( 2022 ), these filters were nonetheless necessary to avoid introducing bias in the estimation of the allelic fraction of the observed changes.…”
Section: Main Textmentioning
confidence: 87%
“…We agree that this can be further optimized and, indeed, subsequent studies proposed more refined approaches to reduce the number of false positive calls (e.g., (Picardi and Mansi 2022 )). It is indeed reassuring that different pipelines converged to the same conclusions (Di Giorgio et al 2020 ; Farkas et al 2020 ; Popa et al 2020 ; Wang et al 2021 ; Graudenzi et al 2021 ; Gregori et al 2021 ; Lythgoe et al 2021 ; Pathak et al 2021 ; Song et al 2021 ; Tonkin-Hill et al 2021 ; Voloch et al 2021 ).…”
Section: Main Textmentioning
confidence: 87%
See 2 more Smart Citations
“…As an example, Hepatitis delta virus uses an ADAR-1 editing mechanism to create the large and short isoforms of the hepatitis delta antigen, both of which are necessary to complete its replication cycle [ 119 ]. In the case of SARS-CoV-2, analysis by NGS of its spike gene [ 120 ] showed that ADAR1 editing was the predominant mechanism generating SARS-CoV-2 genetic variability, although a pattern of nucleotide substitutions suggestive of the ADAR-1 activity was detected only in a small fraction of replicating genomes. However, it seems that the mutations produced by this enzyme were not fixed in the infected human population, suggesting that, by now, nsp12-induced mutations occurring in patients with high viremia and persistent infection would be the main source of new SARS-CoV-2 variants, while those produced by ADAR1 may play an antiviral role [ 120 ].…”
Section: Ngs For Studying Genomic Viral Variabilitymentioning
confidence: 99%